Mechanical resistance comparison between interlocking micro-nail and tension band for fractures subject to muscular flexion forces - Alois Foltran Müller; Silvio Henrique de Freitas; Renata Gebara Sampaio Dória; Julia Belotto Guaraná; Fábio de Souza Mendonça; Atanásio Serafim Vidane; Lázaro Manoel de Camargo; Rachel Santos Bueno Carvalho; Antônio Carlos Shimano; Carlos Eduardo Ambrósio; Bruno Watanabe Minto (Ciência Rural)
ABSTRACT: The ulna, humerus, femur, tibia, and calcaneus fractures repair, which are under constant tension due to exerted forces by the muscle groups adhered thereto, play a key role in the clinical-surgical routine, both in veterinary and human medicine. Therefore, the need for repairing orthopedic procedures is clear. Among the treatment options, the interlocking nail confers rigid stabilization on diaphyseal fractures. It has mechanical advantages over other stabilization techniques, such as plates, compression cortical screws (lag effect), or tension band technique. It was proposed in this study to mechanically compare two fixation methods (interlocking micro-nail or tension band) for fractures under muscular tension. The flexion force was assessed in a universal test machine (EMIC, DL 10000N model), comparing the interlocking micro-nail (IMN) to the tension band (TB) fixation system. The IMN and TB test specimens systems (n=6) went into total failure when the mean maximum force reached 511.20N and 279.90N, and the mean relative stiffness reached 31.33N/mm and 20.97 N/mm, respectively. A significant difference between IMN and TB for the variables maximum strength and relative stiffness were reported (P < 0.01). We concluded that, through mechanical flexion tests, the IMN system has superior resistance compared to the TB system. Thus, the IMN system may be a better option for fixing fractures under muscular tension forces.